Development Of Learning Media Based On Macromedia Flash To Improve The Learning Outcomes Of IPAS Subjects Of Class IV Students Fatahillah Min 2 Jember - Ani Purwatiningsih (Yayasan Insan Mulia Bima, 2024)
Educational media serves as a medium through which teachers deliver learning materials to students, facilitating understanding and assimilation of content. The use of educational media is very important in elementary schools, especially in the context of science learning in class IV Fatahillah MIN 2 Jember. One practical tool that can be used by teachers in teaching science is Macromedia Flash-based learning media. One type of research and development (R&D) approach used in this study is the Borg & Gall model. The test subjects came from fourth grade students of MIN 2 Jember. The material used is the historical stories of the kingdoms in Indonesia in the past through media. Methods such as surveys, exams, observations, and interviews were used to collect data. Quantitative and qualitative data analysis methods, in addition to the T-test, were used in data analysis techniques. With a media design score of 90.6% and an effectiveness level in assisting learning of 92%, the learning media created achieved a content validation level of 93.3%, in line with the findings. Overall, students found the learning media quite interesting, with an attractiveness rate of 82.5%. The average post-test score of 75.9 was much higher than the average pre-test score of 48.7, indicating a considerable improvement in student learning outcomes. There is a chance value of 0.000, which is less than 0.05, in the T-test analysis of this study. Thus, we accept Ha as the alternative hypothesis and reject Ho as the null hypothesis. Thus, it is reasonable to assume that science education can benefit from the incorporation of Macromedia Flash-based learning materials.